2018
DOI: 10.1080/13548506.2018.1468028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mindfulness-based stress reduction on prenatal stress, anxiety and depression

Abstract: Low well-being is common among Chinese pregnant women but few effective interventions currently exist to improve prenatal stress and negative emotions. Mindfulness-based stress reduction (MBSR) has been proved to be effective in reducing stress and rarely studies were focused on Chinese pregnant women. The aim of the current paper is to investigate the effects of 8-week MBSR on prenatal stress, anxiety and depression among Chinese pregnant women. A sample of 66 pregnant women randomly allocated into either the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 9 publications
0
32
1
6
Order By: Relevance
“…RCTs (Krusche et al, 2018;Pan et al, 2018;Zhang et al, 2019) with large sample size, which supported the positive effect of mindfulness intervention on reducing antenatal stress.…”
Section: Summary and Interpretation Of The Findingsmentioning
confidence: 70%
See 2 more Smart Citations
“…RCTs (Krusche et al, 2018;Pan et al, 2018;Zhang et al, 2019) with large sample size, which supported the positive effect of mindfulness intervention on reducing antenatal stress.…”
Section: Summary and Interpretation Of The Findingsmentioning
confidence: 70%
“…Twenty‐eight RCTs reported results of 1944 pregnant women. Nine RCTs were conducted in West Asia (Iran (Asghari et al., 2016; Bastani et al., 2005; Khorsandi et al., 2016; Mohammad & Shima, 2019; Nasiri et al., 2018; Shahtaheri et al., 2016; Zaheri et al., 2017) and Turkey (Ertekin et al., 2018; Fiskin & Sahin, 2018)); seven in Europe (Greece (Kantziari et al., 2019; Tragea et al., 2014), Germany (Richter et al., 2012), Ireland (Matvienko‐Sikar & Dockray, 2017), Sweden (Lönnberg et al., 2020; Scherer et al., 2016) and UK (Krusche et al., 2018)); five in USA (Guardino et al., 2014; Jallo et al., 2014; Urizar et al., 2019; Vieten & Astin, 2008; Zhang & Emory, 2015); three in India (Deshpande et al., 2013; Muthukrishnan et al., 2016; Satyapriya et al., 2009); two in China (Pan et al., 2018; Zhang et al., 2019); and two in Australia (Beattie et al., 2017; Woolhouse et al., 2014). The mean age of the participants ranged from 18 to 35 years old.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One RCT from China tested MBSR among pregnant women and found that there was significant improvement in stress and anxiety symptoms but not on depression. 43 Two other RCTs from Iran demonstrated a beneficial effect of MBCT and MiCBT for depression, anxiety and stress symptoms among pregnant women. 44,45 One RCT from Iran delivered MBSR to adolescent school students and found that there was significant reduction in test anxiety and enhanced emotional regulation after 8 weeks.…”
Section: Screening and Intervention Studiesmentioning
confidence: 99%
“…Bir başka deyişle, gebelerin bilinçli farkındalık düzeyleri arttıkça depresyon, anksiyete ve stres düzeyleri azalmıştır. Gebelerin bilinçli farkındalık düzeyleri ile stres, anksiyete ve depresyon düzeyleri arasındaki ilişkiyi değerlendiren çalışmalarda, benzer şekilde, bilinçli farkındalık düzeyleri arttıkça stres, algılanan stres, anksiyete ve depresyon düzeyleri azalmıştır (6,(16)(17)(18) . Bilinçli farkındalık temelli yaklaşımların uygulandığı çalışmalarda ise gebelerin bilinçli farkındalık düzeylerinin arttığı ve bu duruma bağlı olarak anksiyete, depresyon ve stres düzeylerinin azaldığı belirlenmiştir (19)(20)(21)(22) .…”
Section: Introductionunclassified